A Idealist Veiw of Life. - "Radhakrishnan, S." (London, 1932)
One of the most profoundly religious books of our time - The Spectator Science is a system of second causes, which cannot describe the world adequately, much less account for it. In this remarkable treatise, Radhakrishnan explores aspects of the modern intellectual debate on science vis-a-vis religion and the vain attempts to find a substitute for religion. He discusses, drawing upon the traditions of East and West, the nature and validity of religious experience.Finally, he creates a fine vision of mans evolution and the emergence of higher values. The range of subjects combined with the authors own faith, undogmatic and free of creed, makes this book a philosophical education in itself.
Keywords: Philosophy